Pengembangan Konsep Pariwisata Perkotaan di Jakarta - Tarigan, Emenina; Laksmi, Gratia Wirata; Dewi, Triana Rosalina; Rahmanita, Myrza; Oktadiana, Hera (Jurnal Ilmiah Pariwisata, 2024)
This research examines sustainable tourism development in Jakarta, which faces significant challenges such as environmental pollution, ecosystem damage, and non-integrated policies. The aim of the research is to understand the dynamics of tourism management and the role of society in creating desires. The methods used included in-depth interviews with 30 informants from various backgrounds, focus group discussions (FGD), and participatory observation. The research results show that although it provides economic benefits, its negative impacts on the environment and social life of society must be overcome through collaboration between government, industry and society. Community involvement in tourism planning has proven important to ensure that policies are appropriate to local needs. This research concludes that tourism policy must be more responsive and integrated, by increasing community participation and awareness of desires. Suggestions for the DKI Jakarta government are to develop educational programs that support desires and involve the community in decision making. Tourists are also expected to better appreciate local culture and the environment in their experiences. Through these steps, tourism development in Jakarta can be carried out in a more sustainable and inclusive manner. Keywords: sustainable tourism, community involvement, environmental management